Prison and the Work Ethic - McElligott, Greg (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
Despite persistent depictions to the contrary, coercion pervades the modern work experience and, in many significant respects, is underwritten by the power of the state. This article outlines some of the ways in which long-standing interventions by Canadian (and British) states continue to affect workplace relations today. To appreciate the scope of this effect, it is necessary to trespass across a number of disciplinary boundaries to include topics such as immigration, deportation, political policing, the legal foundations of employment law, the continuing influence of the British Poor Laws, and the role of prisons and prison labour in helping to regulate work standards. States acted to support proletarianization in a comprehensive way, but their tendency to favour large-scale, “labour-saving” building projects has often undermined the actual effectiveness of their efforts at social control. These patterns still haunt prison policy, as I will show toward the end of the article in discussing the Toronto South Detention Centre.